Characterization and potential use of lactic acid bacteria isolated from corn silage - Zakaria, Aida (2011)
Silage, a fermented and high-moisture fodder is an important fodder for large ruminants. Chopped fresh grass, sorghum or whole corn plants were kept under anaerobic conditions to allow the bacteria to convert water-soluble carbohydrates into organic acids. The first objective was to isolate and identify bacteria from corn silage. Taking into consideration the probability and similarity index in the determination of the identification process, five isolates bacteria were isolated and identified by Total Plate Count Technique and Biology Identification System, respectively. Five isolates are Lactobacillus buchneri, Lactobacillus hilgardii, Lactobacillus kefiri, Lactobacillus oris and Lactobacillus rhamnosus. The second objective was to determine the effect of potential bacterial inoculants on fermentation rate and quality of silages. The silage temperature, pH, nutrient digestibility and aerobic stability test for 4 days were determined at 14, 21 and 28 days of ensiling process of the corn plant. Inoculation of lactic acid bacteria significantly improved the fermentation, increased nutrient digestibility and improved aerobic stability of corn silages. There were no significant differences (P>0.05) among the bacterial inoculants in decreasing the pH value of the silages. Addition of bacterial inoculants significantly increased the crude protein (P<0.05) but significantly decreased (p<0.05) the neutral detergent fiber contents with time. The process of fermentation was completed on day twenty-one in all treatment and control (P>0.05). The third objective of this study was to evaluate the digestibility of corn silages treated with bacterial inoculants using in-vitro gas production technique. There were no significant differences in total gas production of 24 hours for 21 and 28 day old corn silages (P>0.05). It was expected that cellulose and hemicelluloses of corn silages crop could be decreased by the enzymes present in the original crop, bacterial action and hydrolysis by organic acid produced during fermentation. This study showed that corn silages inoculated with L. rhamnosus, L. oris and L. buchneri resulted in a higher increasing on the gas production (P>0.05). It is concluded that bacterial inoculants could improve the quality, stability and increase fermentation rate of corn silages. Ensiling for twenty one days was suitable for this silage. Among the five lactic acid bacteria, L. buchneri was identified as the best inoculant to ensile corn forage.